Diagnosis of stator inter-turn short circuit in DTC induction motor drives - Muhamad Farani, Mustafa (2009)
Faults in the stator windings of three-phase induction machines are recognized to play a major role in the failures that occur during the machines life span. The machines (or motors) which were fed by inverters tend to worsen its condition, due to the fast switching of the power semiconductors used by the inverters in which promotes voltage stresses. After a period of time the machines will be affected by the degradation of the stator turns insulation which will eventually lead to winding short circuits. By diagnosing the stator faults in DTC induction motor drives, we can then determine the failures which the information could be used to construct an artificial intelligence system that can help monitor and pin-point the source of motor failure. Thus overcoming the problems is possible and further development of the machines can be done in the near future.